Bone marrow aspirate concentrate with cancellous allograft versus iliac crest bone graft in the treatment of long bone nonunions. Issue 1 (March 2019) - Lin, Kenneth; VandenBerg, James; Putnam, Sara M.; Parks, Christopher D.; Spraggs-Hughes, Amanda; McAndrew, Christopher M.; Ricci, William M.; Gardner, Michael J.
Abstract: Objectives: The purpose of this study was to compare bone marrow aspirate concentrate (BMAC) with cancellous allograft to iliac crest bone graft (ICBG) in the treatment of long bone nonunions. Design: Retrospective cohort study. Setting: A single level I trauma center. Patients: 26 patients with long bone diaphyseal or metaphyseal nonunions with defects >2 mm and treated with open repair and BMAC, compared to 25 patients with long bone diaphyseal or metaphyseal nonunions with defects >2 mm and treated with open repair and ICBG. Intervention: Open repair of long bone nonunion using either autologous ICBG or BMAC with cancellous allograft. Main outcome measure: Nonunion healing, radiographically measured by the modified Radiographic Union Score for Tibia (mRUST) score. Secondary outcomes included risk factors associated with failed repair. Results: The union rates for the BMAC and ICBG cohorts were 75% and 78%, respectively ( P = .8). Infection was the only risk factor of statistical significance for failure. Conclusion: In this study, we found no significant difference in union rate for long bone nonunions treated with ICBG or BMAC with allograft. BMAC and allograft led to 75% successful healing in this series. Given the heterogeneity of the control group and loss to follow-up, further prospective investigation should be conducted to more rigorously compare BMAC to ICBG for nonunion treatment. Level of evidence: III, retrospective cohort.